Static Load Testing Of PCI-Bridges for Assessing Functional Suitability and Its Comparison with Dynamic Testing - Khoeri, Heri; Isvara, Wisnu; Widjajakusuma, Jack; Natasa, Fani; Sofiana, Dini (Universitas Tribhuwana Tunggadewi Malang, 2024)
Â To accommodate the rapid development of residential and commercial areas in the Bumi Serpong Damai (BSD) Region, Banten, the construction of the Kadisurung bridge is necessary to integrate road networks. Before being operational to ensure the safety of bridge users, load testing is conducted. Parameters that must be met in the testing include not exceeding the strain and deflection limits during operational conditions, including when maximum loading occurs. To assess the bridge's performance during operation, research was conducted on both sides of the central span (western side bridge, JSB, and eastern side bridge, JST) with static load testing carried out with gradually increasing loads up to 50% UDL (136 tons), followed by gradual load removal. At JSB, the maximum deflection at 100% UDL, estimated from the deflection at 50% UDL, was 39.92 mm, and at JST, it was 31.67 mm, while the allowable deflection was 43.3 mm. Based on the deflection parameters, the relative capacities of JST and JSB are expressed as 108.5% and 136.7% respectively, relative to their allowable capacities. This indicates that the estimated bridge capacity using static load testing parameters is 6%-10% greater than when using parameters from dynamic load testing. Thus, the bridge is deemed suitable for operation.